A Mathematical Model for the Styrene-Methyl Methacrylate Copolymerization in the Presence of Polybutadiene - Gutierrez, Carolina (2006)
The batch copolymerization of styrene (St) and methyl methacrylate (MMA) in the presence of polybutadiene (PB) is theoretically and experimentally investigated. A mathematical model that enables to calculate the main global variables and the macromolecular structure of the evolving polymer mixture is presented. The model is an extension of that developed by Estenoz et al. (1999) for the homopolymerization of St in the presence of PB. It was validated with experiments that considered diluted solution and bulk copolymerizations carried out at a constant low temperature (65 °C), with THF as solvent, benzoyl peroxide as initiator, and a St-MMA ratio close to the azeotropic composition. For comparison, the solution copolymerization without PB was also considered. All experimental runs were adequately simulated using a single set of kinetic parameters.